The Effect of Employee Competence, Job Placement, and Career Development on Employee Performance at the Medan Belawan Primary Tax Service Office - Setyawan, Rudy; Hasibuan, Rosa Triska Octarini; Wijaya, Rudi; Sadly, M Khairul Fahmi; Supriadi; Syah, Amirul (Asian Journal of Management Analytics, 2024)
This study investigates the influence of employee competency, job placement, and career development on employee performance at the Medan Belawan Pratama Tax Service Office. The survey method is used to collect data from respondents who are tax officials. The results of multiple regression analysis show that employee competency, job placement, and career development have a significant influence on employee performance. These findings highlight the importance of competency development, appropriate placement, and career development programs in improving employee performance in government institutions. Managerial implications and recommendations for future research are also discussed.